Asthma and exercise‐induced bronchoconstriction in athletes: Diagnosis, treatment, and anti‐doping challenges - Hostrup, Morten; Hansen, Erik S. H.; Rasmussen, Søren M.; Jessen, Søren; Backer, Vibeke (Scandinavian journal of medicine & science in sports, 2024)
Athletes often experience lower airway dysfunction, such as asthma and exercise‐induced bronchoconstriction (EIB), which affects more than half the athletes in some sports, not least in endurance sports. Symptoms include coughing, wheezing, and breathlessness, alongside airway narrowing, hyperresponsiveness, and inflammation. Early diagnosis and management are essential. Not only because untreated or poorly managed asthma and EIB potentially affects competition performance and training, but also because untreated airway inflammation can result in airway epithelial damage, remodeling, and fibrosis. Asthma and EIB do not hinder performance, as advancements in treatment strategies have made it possible for affected athletes to compete at the highest level. However, practitioners and athletes must ensure that the treatment complies with general guidelines and anti‐doping regulations to prevent the risk of a doping sanction because of inadvertently exceeding specified dosing limits. In this review, we describe considerations and challenges in diagnosing and managing athletes with asthma and EIB. We also discuss challenges facing athletes with asthma and EIB, while also being subject to anti‐doping regulations.